Formative Assessment as an Evaluation Tool for Elementary Students’ Speaking Skills in Indonesian Language Learning: A Descriptive Qualitative Study - Ikrima Maulida; Eci Lestari; Cut Kumala Sari; Lhutfia Wahyu Safutri (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Assessment of speaking skills must be conducted objectively, systematically, and thoroughly to provide students with appropriate feedback that can improve their performance. One recommended form of authentic assessment is formative assessment. This study aims to analyse the implementation of formative assessment in evaluating the speaking skills of fourth-grade elementary school students in Indonesian language learning, using a qualitative descriptive approach with data collected through observation, interviews, documentation, and rubric-based assessment. The participants comprised one teacher and thirty students, with four selected for in-depth interviews. The findings revealed that formative assessment was implemented systematically through criteria-based rubrics, oral and written feedback, observation notes, and student reflection. Most students achieved speaking scores in the good to very good category, particularly in content and fluency. Formative assessment helped students gradually identify their weaknesses, improve their speaking performance, and develop reflective learning awareness. The results of this study support the use of formative assessment as a constructive evaluation approach in elementary-level language learning.